Optical discrete solitons in waveguide arrays. I. Soliton formation - Eisenberg, H. S.; Morandotti, R.; Silberberg, Y.; Arnold, J. M.; Pennelli, G.; Aitchison, J. S. (J. Opt. Soc. Am. B, JOSAB, 2002)
We investigate the generation of discrete spatial solitons in arrays of coupled waveguides. Light was launched into the center of the array, and different beam sizes and array geometries were tested. At low power, the propagating field spreads as it couples to more waveguides. When the intensity is increased, localization is observed around the input waveguides, leading to the formation of a discrete soliton. For wide input beams, exciting a few waveguides, soliton splitting, which is due to instability induced by multiphoton absorption, is observed. All of these effects are described well by a coupled-mode formalism.
Publisher: Optica Publishing Group
Keywords: Dark solitons; Nonlinear absorption; Optical parametric oscillators; Optical systems; Spatial solitons; Waveguide modes